Relationship between share index volatility, basis and open interest in futures contracts: The South African experience - B. Motladiile; E. V.D.M. Smit (South African Journal of Business Management, 2003)
In a rational efficiently functioning market, the price of the share index and share index futures contracts should be perfectly contemporaneously correlated. However, in practice the cost of carry model is obscured as the basis varies and is normally not equal to the cost of carry.This study uses the Chen, Cuny and Haugen (1995) model to examine the relationship between the basis and volatility of the underlying index and between the open interest of the futures contract and the volatility of the underlying index. The tests were performed on data from ALSI, FINI and INDI futures contracts. The sample period was from January 1998 to December 2001.The results confirm the conclusion of Chen et al. (1995) who found the basis to be negatively related to the volatility of the underlying index. The other main prediction of the Chen et al. (1995) model, which is also supported by the current study, is that open interest is significantly related to the volatility of the underlying index. The results further support the proposition of Helmer and Longstaff (1991) of a highly significant negative concave relationship between the basis and the interest rate.
Keywords: 650